Coffee Machine: a social virtual environment for informal collaboration. - Davi D'Andréa Baccan (2005)
Human beings need to collaborate with each other whether the goal is to develop a jointly collaborative task, to maintain existing social relationships or to provide opportunities to create new ones. These collaborations can be essentially classified either in formal or informal collaborations. These are two distinct but complementary forms of collaborations. When participants are engaged in a formal collaboration they explicitly agree in advance what will be discussed, when, and where it will take place. On the other hand, informal collaboration consists in spontaneous and not planned collaborations that occur countless times and in a transparent way in the everyday life. In addition, informal collaboration is intimacy related to physical proximity. Indeed, the opportunities for informal collaboration rely on the physical proximity of its participants. In this context, the main goal of this research is to investigate what features of informal interactions in the everyday life could be used to build a social virtual environment in order to provide, foster and mediate informal collaboration between participants of geographically distributed groups. Therefore, this research presents an investigation of what are the features of informal collaborations, including the understanding of awareness, public and private spaces, and how to deal with the tradeoff between providing awareness information and securing the privacy of individuals. In addition, it discusses how people interact with each other in the everyday life by presenting what is the importance of physical spaces not only for the informal collaboration but also in general, what are the features of spaces, and what it offers for informal collaborations. Based on these understandings, a PrAPI (Presence, Awareness, Privacy, Interactivity) model was conceived to address the problem. Furthermore, to provide a deeper investigation, a prototype version called Coffee Machine environment was designed and developed in accordance with this model. Finally, this prototype was tested and evaluated by participants of geographically distributed groups.